3-DOF planar parallel-wire driven robot with an active balancer and its model-based adaptive control. (18th July 2018) - Kino, H.; Yoshitake, T.; Wada, R.; Tahara, K.; Tsuda, K.
ABSTRACT: This paper has proposed a parallel-wire driven robot (PWDR) with an active balancer, which is notably useful for such applications as ceiling maintenance and object conveyance near a ceiling in a factory. Because this robot is an under-actuated system, the uncertainty of the inertial parameters of the load strongly affects the resultant motion and reduces the control accuracy because of the dynamics interference. However, to date, the dynamics of this robot has not been thoroughly elucidated. Thus, this study analyzes the dynamics of a PWDR that controls three degree-of-freedom using two wires and an active balancer. Moreover, based on the dynamic analysis, a model-based adaptive controller for the parameter uncertainty of a load is proposed, and its effectiveness is demonstrated through simulation. GRAPHICAL ABSTRACT: